Hubungan Pola Makan dengan Kejadian Gastroesophageal Reflux Disease pada Mahasiswa di ITSK RS dr.Soepraoen Malang - Alaya, Vandela Nikita; Permata, Agung; Rahmawati, Siti (Journal Syifa Sciences and Clinical Research, 2025)
College students are a vulnerable group that experiences gastroesophageal reflux disease (GERD), because it is influenced by factors such as psychological stress and unhealthy eating habits. Factors that make students susceptible to GERD are influenced by unhealthy eating habits. This is caused by a fairly heavy academic load, such as a busy lecture schedule, high frequency of exams and assignments, and limited rest time. This disease is characterized by the entry of stomach acid into the esophagus, which is caused by dysfunction in the lower part of the esophagus. which is characterized by symptoms of chest pain such as heartburn, regurgitation, difficulty swallowing, and sore throat. This condition contributes to digestive system disorders, so that the incidence of GERD is increasing. This study aims to reveal the relationship between diet and the incidence of gastroesophageal reflux disease (GERD) among college students. This study applies a non-experimental correlative quantitative approach and uses a cross-sectional design. Data were collected using a purposive sampling technique, involving 75 respondents who were final year students at the Faculty of Science and Health, dr. Soepraoen Hospital Malang. The measuring instruments used in this study were the Gastroesophageal Reflux Disease Questionnaire (GERDQ) and the Diet History Questionnaire (DHQ), which were distributed via Google Form. The results of the statistical analysis showed that 30 students (40.00%) had gastroesophageal reflux disease (GERD), 45 students (60.00%) did not have GERD, while 32 students (42.67%) had poor diet and 43 students had good diet with a percentage (57.33%). Data analysis using the Spearman rank correlation test found that there was a significant relationship between diet and the incidence of GERD, with a significance value of 0.000, 0.05. The results of the indicated correlation strength were strong, with a value of 0.638